The Future of the Welfare State - COLLINS, MICHEAL (Social Justice Ireland, 2010)
The welfare state is not an end in itself. It is a means to an end ? the wellbeing of all people. The future of the welfare state has been a topic of discussion and argument for more than 30 years on issues ranging from education to employment, from healthcare to social housing, from welfare rates to pensions to provision for people with disability. Some have claimed it cannot survive because the population is aging. Others have argued that globalisation will undermine it in due course. Recent economic upheavals and huge budget cutbacks in many countries have added to the questions faced by the welfare state. Is the welfare state really under threat? Has the era of the welfare state passed? Will people continue to support it? What are the major challenges faced by the welfare state at this time? What impact does the welfare state have on reducing poverty? Can the necessary funding be provided? If the welfare state is to survive how should it adjust to the changing economic situation? What are the implications of demographic developments? What should be the core of the welfare state if it is to persist in the twenty first century? Can the nation state continue to be the basis for this kind of development model, this kind of social contract? In these economically turbulent times it is essential to focus on the shape of the society we wish to see emerge. The welfare state has been in existence in Ireland for about a century. Do we wish to see it continue? If so, what form should it take? What are the key challenges it faces in Ireland? How might these be addressed effectively and efficiently? Should people?s expectations of the welfare state change? The chapters in this book, which were first presented at a policy conference on the topic of The Future of the Welfare State, seek to address some of the key questions and issues that emerge in this context.
PUBLISHED
Keywords: Welfare State; Ireland; Welfare State; Ireland